Signal of Crimes: Worries Over Foreign Immigrant’s Threats - Ahmad, Za’im; Chulan, Majdah; Isa, Yusramizza Md (International Journal of Psychosocial Rehabilitation, 2020)
This study was aimed at identifying the criminal worries among respondents towards foreign immigrants, which acted as a of criminal occurrence. It also examined the relationship between foreign immigrants and criminal worries. The data collection involved 400 respondents in Penang, Malaysia. A questionnaire was utilized as the instrument of the study. The findings are divided into three sections: i) the perceptions of the respondents to criminal worry involving foreign immigrants, ii) the mean difference of socio-demographic factors with foreign immigrants by t-test and ANOVAs iii) the relationship between the aspect of foreign immigrants and criminal worries. The results of study are presented using both descriptive and inferential statistics. The study suggests some significant practical actions that need to be undertaken to control and monitor the foreign immigrantin Malaysia.